Raphidiopsis mediterranea (Nostocales) exhibits a flexible growth strategy under light and nutrient fluctuations in contrast to Planktothrix agardhii (Oscillatoriales) - Aguilera, Anabella (2019)
Raphidiopsis mediterranea is a freshwater cyanobacterium that forms toxic blooms in eutrophic water bodies. Factors controlling its proliferation have not been explored in detail. We investigated R. mediterranea autecology by (i) analyzing its dynamics in a hypertrophic shallow lake dominated by Planktothrix agardhii (Oscillatoriales) and its relationship with environmental factors; and (ii) studying the effect of light intensity and phosphate availability on R. mediterranea isolates growing in mono or in co-cultures with P. agardhii. The redundancy analysis demonstrated that water temperature, light, and phosphate concentrations were important driving factors for the seasonal succession of the two species. When grown together with P. agardhii, R. mediterranea growth was strongly promoted under the highest light intensity treatment. On the other hand, in monoalgal cultures under phosphorus starvation, both strains exhibited a significant increase in total alkaline phosphatase activity, and changes in the expression of homologs to phoA-like and phoD genes (members of the Pho regulon). However, R. mediterranea showed higher phosphatase activity than P. agardhii, suggesting greater tolerance to phosphate limitation. Taken together, we conclude that physiological features of R. mediterranea play an important role in the coexistence with P. agardhii under environmental changes.